The Relationship between managers\' leadership style and employees\' creativity in Qazvin hospitals - Ali mohammad Mosadegh Rad; Maryam Saadati (Tehran University of Medical Sciences, 2016)
Background: Providing high quality, safe and effective health care services requires competent and motivated employees. Employee's creativity plays a significant role in motivation and health care system productivity. Various individual and organizational factors influence employees' creativity. This study aimed to examine the relationship between managers' leadership style and employees' creativity in Qazvin hospitals. Materials and Methods: Creativity and leadership questionnaires were used to conduct this descriptive and cross-sectional study. The questionnaires were distributed among 800 employees in ten hospitals using stratified sampling method. Descriptive and analytical methods utilized for data analysis using SPSS software. Results: The mean score of hospital employees' creativity was 47.5 out of 60 (moderate level). The prevalent leadership style of managers was transformational. There was a significant statistical association between employees' creativity and managers' transformational leadership style. Since, leadership styles of hospital managers influence employees' creativity, they have to apply appropriate leadership style to motivate employees and develop their creativity in order to improve hospital productivity.